The Effect of Black Cumin (Nigella sativa) Oil Supplementation on Hematotoxicity Induced by Benzene in Gasoline Vapors from Gas Stations in Male Wistar Rats - Ikhram Hardi S; Merryana Adriani; Tri Martiana (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aimed to prove the effect of black cumin oil supplementation through analysis of levels of CYP2E1, MDA, GSH, and hematological profiles in experimental animals, Wistar rats, which were exposed to benzene in gasoline vapors from gas stations. Sixty-four experimental Wistar rats were divided into eight groups with eight rats each, two control groups (C1 and C2), and six experimental groups (T1, T2, T3, T4, T5, and T6). Blood samples of experimental rats were taken through intracardiac with ketamine-xylazineacepromazine anesthesia on day 15 for group C1, C2, T1, T3, and T5; and day 29 for group T2, T4, and T6. The ELISA method measured the levels of CYP2E1, GSH, and MDA in this study, while the hematological profile used a hematology analyzer. This study indicates that benzene in gasoline vapors exposure caused significant hematotoxicity (P <0.05). Supplementation of black cumin seed oil at a dose of 2.5 ml/kg, 5 ml/kg, and 10 ml/kg, all of which have the potential to provide a protective effect against the hematotoxicity of benzene in gasoline vapors through increased internal antioxidants (GSH). The GSH can play a role in the mechanism of vapor metabolism of substances in gasoline vapors in the body through decreased CYP2E1 levels and decreased MDA levels. Further research is still needed with a more extended treatment duration to ascertain the chronic effects of benzene hematotoxicity on the genomic pathway to assess black cumin’s role, whether in the form of oil, powder, or other forms of extraction.